Stage-Dependent Changes of Visual Function and Electrical Response of the Retina in the rd10 Mouse Model - Cha, Seongkwang; Ahn, Jungryul; Jeong, Yurim; Lee, Yong Hee; Kim, Hyong Kyu; Lee, Daekee; Yoo, Yongseok; Goo, Yong Sook (Frontiers in Cellular Neuroscience, 2022)
One of the critical prerequisites for the successful development of retinal prostheses is understanding the physiological features of retinal ganglion cells (RGCs) in the different stages of retinal degeneration (RD). This study used our custom-made rd10 mice, C57BL/6-Pde6bem1(R560C)Dkl/Korl mutated on the Pde6b gene in C57BL/6J mouse with CRISPR/Cas9-based gene-editing method. We selected the postnatal day (P) 45, P70, P140, and P238 as representative ages for RD stages. The optomotor response measured the visual acuity across degeneration stages. At P45, the rd10 mice exhibited lower visual acuity than wild-type (WT) mice. At P140 and older, no optomotor response was observed. We classified RGC responses to the flashed light into ON, OFF, and ON/OFF RGCs via in-vitro multichannel recording. With degeneration, the number of RGCs responding to the light stimulation decreased in all three types of RGCs. The OFF response disappeared faster than the ON response with older postnatal ages. We elicited RGC spikes with electrical stimulation and analyzed the network-mediated RGC response in the rd10 mice. Across all postnatal ages, the spikes of rd10 RGCs were less elicited by pulse amplitude modulation than in WT RGCs. The ratio of RGCs showing multiple peaks of spike burst increased in older ages. The electrically-evoked RGC spikes by the pulse amplitude modulation differ across postnatal ages. Therefore, degeneration stage-dependent stimulation strategies should be considered for developing retinal prosthesis and successful vision restoration.